Theoretical Study for the Electron Drift Velocity in Sf6 Gas and Its Mixture with Nitrogen - Majeed, Ra`ad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Calculations and predication a theoretical formulas for the electron drift velocity in a gas medium are achieved to deduced the electron distribution function for different gas concentrations. The calculations are achieved by using the numerical solution for  Boltzmann transport equation in two term approximation, using the NOMAD  program for the drift velocity in a gas medium. It's necessary to note that the solution is essentially depending upon the elastic and inelastic collision cross section. In order to fixe a good accuracy for the using cross section it's necessary to calculate the electron distribution function and therefore study their behavior. Results about the electron drift velocity show that a decreasing profile with the increase of the SF6 gas concentration. And also an increasing profile for the drift velocity related to a high nitrogen concentrations. The important applications for these gases are in using them as an insulator in electrical transformers and generators.